2002
DOI: 10.1046/j.1471-4159.2002.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid catabolism: roles for neprilysin (NEP) and other metallopeptidases?

Abstract: The steady-state level of amyloid b-peptide (Ab) represents a balance between its biosynthesis from the amyloid precursor protein (APP) through the action of the b-and c-secretases and its catabolism by a variety of proteolytic enzymes. Recent attention has focused on members of the neprilysin (NEP) family of zinc metalloproteinases in amyloid metabolism. NEP itself degrades both Ab 1)40 and Ab 1)42 in vitro and in vivo, and this metabolism is prevented by NEP inhibitors. Other NEP family members, for example … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
156
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(161 citation statements)
references
References 81 publications
(149 reference statements)
2
156
2
1
Order By: Relevance
“…Because PAO accumulation is directly correlated with the severity of cardiac disease (15), we examined the potential causes for its accumulation. Recent data indicate that amyloid-rich neural samples from patients with neurodegenerative disease show significantly reduced levels of the metallomembrane endopeptidase neprilysin (23)(24)(25). The formation of amyloid and preamyloid depositions can be enzymatically regulated by this enzyme (23), and we hypothesized that PAO accumulation in the hearts of CryAB R120G mice might be partially dependent on diminished neprilysin activity.…”
Section: Resultsmentioning
confidence: 96%
“…Because PAO accumulation is directly correlated with the severity of cardiac disease (15), we examined the potential causes for its accumulation. Recent data indicate that amyloid-rich neural samples from patients with neurodegenerative disease show significantly reduced levels of the metallomembrane endopeptidase neprilysin (23)(24)(25). The formation of amyloid and preamyloid depositions can be enzymatically regulated by this enzyme (23), and we hypothesized that PAO accumulation in the hearts of CryAB R120G mice might be partially dependent on diminished neprilysin activity.…”
Section: Resultsmentioning
confidence: 96%
“…In normal brains, Aβ is degraded by multiple peptidases, including neprilysin, endothelin-converting enzyme and insulin-degrading enzyme. 21 While Aβ is commonly thought of as the main toxic agent in AD, there is emerging evidence of a normal physiological role for the peptide in the regulation of neuronal calcium and potassium channel currents. 22,23 This, therefore, indicates that Aβ should only be considered as a toxic agent when levels increase as a result of an imbalance in its production and degradation/ clearance, such as occurs in AD.…”
Section: Regulates the β-Secretase Cleavage Of Appmentioning
confidence: 99%
“…The targets of M13 members usually are bioactive peptides with a key function in the regulation of cardiovascular, nervous, and immune systems (Turner et al , 2001 ). Zmp1 shares particularly primary sequence similarity (48 % ) with human neprilysin (NEP; 749 aa), an extracellular peptidase that preferentially hydrolyzes extracellular oligopeptides ( < 5 kDa) on the amino side of hydrophobic residues (also including amyloid β peptides implicated in Alzheimer disease) (Carson and Turner , 2002 ;Madani et al , 2006 ). We recently solved the crystal structure of Zmp1, and our investigation demonstrated that Zmp1 and NEP are also structurally conserved (Ferraris et al , 2011 ).…”
Section: Introductionmentioning
confidence: 99%